Chemical reactions at the graphitic step-edge: changes in product distribution of catalytic reactions as a tool to explore the environment within carbon nanoreactors - Lebedeva, Maria A.; Chamberlain, Thomas W.; Thomas, Alice; Thomas, Bradley E.; Stoppiello, Craig T.; Volkova, Evgeniya; Suyetin, Mikhail; Khlobystov, Andrei N. (Royal Society of Chemistry, 2016)
A series of explorative cross-coupling reactions have been developed to investigate the local nanoscale environment around catalytically active Pd(II)complexes encapsulated within hollow graphitised nanofiber (GNF). Two new fullerene-containing and fullerene-free Pd(II)Salen catalysts have been synthesised, and their activity and selectivity towards different substrates has been explored in nanoreactors. The catalysts not only show a significant increase in activity and stability upon heterogenisation at the graphitic step-edges inside the GNF channel, but also exhibit a change in selectivity affected by the confinement which alters the distribution of isomeric products of the reaction. Furthermore, the observed selectivity changes reveal unprecedented details regarding the location and orientation of the catalyst molecules inside the GNF nanoreactor, inaccessible by any spectroscopic or microscopic techniques, thus shedding light on the precise reaction environment inside the molecular catalyst-GNF nanoreactor. Keywords: nanoreactor, catalysis, fullerene, salen, cross-coupling